2021
DOI: 10.1111/vde.12971
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous microRNA expression in healthy Labrador and Golden retrievers and retrievers with allergic and inflammatory skin diseases

Abstract: Background -MicroRNAs (miRNA) are short, single-stranded RNA molecules that regulate gene expression in a post-transcriptional manner. Their expression is proposed to be tissue-specific and alterations in miRNA expression have been detected in many diseases.Objective -To compare miRNA expression in the skin of healthy Labrador and golden retrievers, and those with allergic and nonallergic dermatitis.Methods and materials -Formalin-fixed and paraffin-embedded (FFPE) skin specimens from seven healthy Labrador an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Potential genetic biomarkers of cAD are miR-141, miR-187, miR-200a, miR-203, miR-215 and miR-429, and the genes PDE4D, PIAS1, RORA and SH2B1. [22][23][24] However, further studies are needed to confirm that these genetic biomarkers are specific to cAD and not an upregulation caused by other nonallergic inflammatory skin responses. The protective or detrimental role of environmental factors such as living environment during early life, and exposure to bacterial, fungal and parasitic components have undergone continued investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential genetic biomarkers of cAD are miR-141, miR-187, miR-200a, miR-203, miR-215 and miR-429, and the genes PDE4D, PIAS1, RORA and SH2B1. [22][23][24] However, further studies are needed to confirm that these genetic biomarkers are specific to cAD and not an upregulation caused by other nonallergic inflammatory skin responses. The protective or detrimental role of environmental factors such as living environment during early life, and exposure to bacterial, fungal and parasitic components have undergone continued investigation.…”
Section: Discussionmentioning
confidence: 99%
“…23 In a more recent study in golden and Labrador retrievers, 18 selected miRNAs were compared between atopic dogs, dogs with nonallergic inflammatory skin diseases and a group of healthy dogs. 24 Four miRNAs (miR-142, miR-146a, miR-155 and miR-21) were overexpressed in the atopic compared to the healthy dogs. However, the same miRNAs were overexpressed in a similar way in other nonallergic inflammatory skin samples, suggesting that those miRNAs have a rather general role in the inflammatory skin response rather than being associated with atopic disease or an allergic reaction.…”
Section: Biomarkersmentioning
confidence: 95%
See 1 more Smart Citation
“…This is the first study to report the role of miR-1839 in rats. Previous studies have shown that miR-1839 is a highly conserved lncRNA in pigs and dogs [ [24] , [25] , [26] ], and some studies have shown that miR-1839 is significantly altered in allergic and inflammatory skin [ 27 ], suggesting a strong association between miR-1839 and inflammation and immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a review mentioned that miR-193b-3p level was downregulated in allergic diseases but did not provide substantial evidence [9]. In addition, miR-193b was notably underexpressed in the allergic dermatitis group compared to healthy controls [10]. Yet the function and specific mechanism of miR-193b-3p in AR have hardly been reported currently.…”
Section: Introductionmentioning
confidence: 98%